Water Security in the Euphrates-Tigris Basin - Lorenz, Frederick Michael (University of Washington Water Center, 2009)
In a time of international tension and insecurity, water will become increasingly important, particularly in the arid lands of the Euphrates-Tigris. One of the security challenges, not often discussed, is the long range prospect for Iraq to have adequate water to reach a basic level of stability and prosperity. Turkey's dams and irrigation systems pose a substantial threat, and more needs to be done to increase cooperation on water resources in the region.
Keywords: Iraq; water resources; water rights; water management; water supply; water policy; water distribution; water allocation; arid lands; Turkey (country)